إيقونة الراعي الصالح من خلال بعض التوابيت الرومانية بالجزائر - بن علال,نصيرة (University of Eloued جامعة الوادي, 2023)
تحتل التوابيت بصفة عامة مكانة خاصة، نظرا لما تحمله من زخارف متنوعة، حيث يعتبر هذا النوع من المدافن من بين أهم الوثائق الأثرية التي تم اللجوء إليها من أجل التعبير عن مكنوناتهم الدينية والجنائزية وبراعتهم الفنية، سواء كانت هذه المكنونات متعلقة بالحياة اليومية: كمواضيع الرعي، الصيد، الوقائع الحربية، عقود الزواج، أو تلك المتصلة بالحياة الدينية: كالمواضيع الميتولوجية والمسيحية وغيرها من المواضيع الزخرفية الأخرى. يهتم موضوعنا هذا بدراسة بعض النماذج التي تحمل موضوع الراعي الصالح، الذي يعتبر من بين الزخارف المسيحية الأكثر رواجا في الأقطار المتأثرة بالحضارة الرومانية، حيث نجدها تغزوا مجموعة متنوعة من التوابيت باعتبارها المأوى الأخير لجثمان المتوفين. The ornate sarcophagi are considered among the most important archeological documents, through which the ancients expressed their religious beliefs, and their artistic prowess. Rich in their iconographic corpus linked to everyday life, such as grazing scenes, hunting war scenes, marriage contracts, or those linked to religious life, in which mythological themes occupy a very large place. Indeed, the present study includes three pieces of unequal importance, bearing on their front faces one of the most widespread Christian themes in North Africa, that of the good shepherd. Our choice fell on this subject, because of the deep significance of this theme linked to the Christian faith inspired by the Torah and the Gospel and on the other hand, because of the difference in the models available to us, in terms of their general shape and the materials used in their construction.
Keywords: sarcophagus; Sculpture; iconography; the good shepherd; funeral Art; الفن الجنائزي; النحت; تابؤت